Crafting Effective ESP Writing Instructions: A Comprehensive Need Analysis - Handayani, Riris; Sukarno, Sukarno; Ciptaningrum, Dyah Setyowati; Titania, Fani Nabila; Rihatmi, Rihatmi; Sharizan, Sharizan (International journal of multicultural and multireligious understanding, 2025)
Writing is assumed as the most challenging skill for EFL students and teaching writing for ESP and EGP needs different approaches. This preliminary study aims to reveal students’ problems and needs to find out effective teaching writing instructions. This descriptive study involved the tenth-grade students of culinary art class at SMK N 2 Godean. 28 students and an English teacher participated in voicing their needs concerning the writing skill instructional materials. The data were collected through a writing test, a close-ended questionnaire survey, and a semi-structured interview. The questionnaire data was analyzed using descriptive statistics, while interview data was transcribed, categorized, and interpreted (Alwasilah, 2002). Additionally, the writing test results were evaluated using Fitriani's (2020) writing rubric assessment. The result showed that students need innovative teaching instructions that are suitable to their major and effective in improving their writing abilities, especially in the aspects of vocabulary, grammar, and structure. Moreover, the teacher also has limited resources in designing specific materials and bringing innovations into the classroom. This problem resulted in poor students’ English proficiency and low motivation in writing. Based on that, this study has the potential to bridge the gap by identifying students' needs and providing recommendations for designing effective ESP writing instruction.